(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Hepatitis E virus (HEV) infection is responsible for more than half of acute viral hepatitis (AHV) with high feto-maternal complications. Bangladesh has high prevalence of HEV infection among pregnant women. This study was undertaken to observe fetal -maternal outcome of HEV infection in Bangladeshi pregnant women . For this purpose a total of 56 pregnant women with AVH were enrolled from two tertiary care hospitals of Dhaka, Bangladesh. Blood samples were collected and tested for HEV Ig-M, HBsAg and Anti HCV. Thirty one pregnant women were tested positive for HEV Ig-M, acted as case and rest 25 women had viral hepatitis other than HEV, acted as control group (non-HEV). Among the HEV infected pregnant women, 38.7% of the patients (12/31) were aged between 21-25 years with mean age of 23.7 + SD 4.5 years. Twelve (39%) AVH-E patient died due to fulminant hepatic failure (FHF), hepatic encephalopathy (HFE) and multiorgan dysfunction. Maternal mortality due to HEV was greater [ (RR), 9.6; 95% CI, 1.3 to 69.5] in HEV infected women than in non- HEV infected women and it was higher in 2nd trimester (55.5%) then the 1st and 3rd trimester of pregnancy. Babies born to pregnant women with acute Hepatitis due to HEV (AHV-E) were more likely to have intrauterine death (RR 18.68; p = 0.03) and preterm delivery (RR 7.25; p = 0.05) than the non-HEV infected pregnant women. Only 23% (7/31) babies reached up to term maturity. In conclusion, his study reveals that comparing with non-HEV infection, pregnant women with AHV-E infection causes worse feto-maternal outcomes especially in the second trimester of pregnancy which needs special attention of healthcare providers to reduce bad obstetric outcome in HEV endemic countries. Bangladesh J Med Microbiol 2015; 9 (2): 3-6